Working toward a transdisciplinary approach to teaching and learning planetary health–A collective reflection - Dambre, Cato; Strack Diaz, Julia Gabriela; Orhan, Rana; Montag, Doreen; van der Zande, Indira; Gallo, Valentina (Frontiers in Public Health, 2022)
Background – In order to educate the next generation of leaders to work at reverting the damaging effects of the Anthropocene, there is an increasing need to incorporate more environmental-related aspects in all teaching programmes, including the health-related. Planetary health is a complex field which can benefit from a transdisciplinary pedagogical approach. The aim of this research was to evaluate a transdisciplinary course taught at the Bachelor degree Global Responsibility & Leadership of the University of Groningen through substantive feedback and reflections from the students. Methods – By the end of the course, a focus group was conducted with the students inviting them to reflect on the different aspects of the pedagogical approach, evaluating their effectiveness. A thematic analysis was conducted on the transcribed focus group. Results – The students appreciated the added value of transdisciplinary and peer-to-peer learning and teaching adopted in the Planetary Health course, as a way of enhancing their learning experience. They pointed out the need of incorporating a transcultural approach into the transdisciplinary one, as a way not only to improve their learning experience, but also to enrich the transdisciplinarity itself. Conclusion - Incorporating transdisciplinary and transcultural teaching of planetary health into undergraduate programmes was found to be of added value. The peer-to-peer horizontal learning opportunities were seen as a way for taking advantage of the collaborative, informal teaching and community building serving the overall scope of the course .